2013
DOI: 10.1016/j.ijnt.2013.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Skull base fractures: An institutional experience with review of literature

Abstract: Fractures of the skull base are relatively common. They have been reported to occur in 3.5?24.0 percent of head injury patients. This wide variation results from differences in studied patient populations and from difficulty of obtaining radiographic verifications of the fracture.1 The Traumatic Coma Data Bank in a prospective series of severe head injury reported that 25% had basilar skull fractures.2 In this paper we analyze the various types of fractures and their management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 26 publications
2
12
0
6
Order By: Relevance
“…This has been implicated in approximately 4% of TBIs [ 3 ], and also accounts for about 19% of all skull fractures [ 11 ]. In addition, blunt trauma is accountable for over 90% of all SBF's [ 12 ], with most injuries located in the anterior fossa (51%) [ 13 ]. Faried et al, reported on the occurrence of around 69.4% of cases in the anterior fossa, while 27.5% was in the middle cranial fossa [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been implicated in approximately 4% of TBIs [ 3 ], and also accounts for about 19% of all skull fractures [ 11 ]. In addition, blunt trauma is accountable for over 90% of all SBF's [ 12 ], with most injuries located in the anterior fossa (51%) [ 13 ]. Faried et al, reported on the occurrence of around 69.4% of cases in the anterior fossa, while 27.5% was in the middle cranial fossa [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Faried et al, reported on the occurrence of around 69.4% of cases in the anterior fossa, while 27.5% was in the middle cranial fossa [ 14 ]. Mokolane et al described the center area as the most common target point, and is assumed as the weakest area, due to the presence of neurovascular foramina and thin bones [ 13 , 15 ]. However, the most frequently fractured spots, as observed in 14–22% of all cases were in the temporal bone or laterobasal fractures, resulting from high energy blunt impact [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common mechanisms of head injury are motor vehicle accidents (which account for 40% in both the adults and children), followed by falls, direct trauma by falling/penetrating ob jects, and assaults. 1,4 In the pediatric population, SBFs are caused by falls from heights (32%), falls on the ground (10%), falls related to sports (3%), and epi sodes of violence (8%) 4 (for the pediatric skull base traumatology, see page 876).…”
Section: ■ ■ Causesmentioning
confidence: 99%
“…1 • SBFs can cause death or coma. They may be associated with immediate or delayed complications, such as cerebrospinal fluid (CSF) leakage, possible men ingitis, and neurovascular damage (injury of arteries, dural sinuses, and/or cranial nerves).…”
mentioning
confidence: 99%
“…Any fracture occurring in this region or propagating to this region is called basilar skull fracture [27]. BSF can be caused by direct impacts at the base of the skull or by remote impacts [28,29], such as craniofacial impacts, which frequently occur in motorcycle accidents [22] and can lead to BSF [30,31]. Cooter and David [30] postulated that the impact load due to the blows on the full-face helmet's chin bar can be transmitted to the base of skull via the chin strap and lead to BSF.…”
Section: Introductionmentioning
confidence: 99%